2022
DOI: 10.1111/jerd.12944
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue resistance and fracture strength of narrow‐diameter one‐piece zirconia implants with angled abutments

Abstract: Objective: Zirconia implants are assumed to satisfy the esthetic requirements that titanium implants cannot meet, however, there are not enough studies in the literature about narrow-diameter and angled zirconia implants that can be preferred especially in the anterior region. This in vitro study aimed to evaluate the fatigue resistance and fracture strength of narrow-diameter zirconia implants with angled abutments. Materials and Methods: Forty-eight one-piece experimental zirconia implants and monolithic zir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
(164 reference statements)
1
4
0
Order By: Relevance
“…The objective of this work was to conduct a comparative study and mechanically characterize new materials that are potential candidates for dental implantology. The obtained results agree with those of previous studies [ 19 , 22 , 23 ]. Sivrikaya et al found that zirconia abutments showed a lower stress distribution compared to that of titanium abutments, indicating that zirconia abutments may be a better choice for dental implants in patients who exhibit parafunctional habits.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The objective of this work was to conduct a comparative study and mechanically characterize new materials that are potential candidates for dental implantology. The obtained results agree with those of previous studies [ 19 , 22 , 23 ]. Sivrikaya et al found that zirconia abutments showed a lower stress distribution compared to that of titanium abutments, indicating that zirconia abutments may be a better choice for dental implants in patients who exhibit parafunctional habits.…”
Section: Discussionsupporting
confidence: 93%
“…Technical complications are quite common in implant-supported restorations and might strongly affect the patients’ comfort and satisfaction with their oral rehabilitation. Therefore, it is crucial to thoroughly examine the mechanical properties of restorative materials intended for use in implant dentistry, particularly when they are subjected to cyclic loading conditions [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…An in vitro study, published after the aforementioned review, evaluated and compared the fatigue resistance and fracture strength of zirconia implants of different diameters (3.0 and 3.7 mm), with straight or 15°-angled abutments. It was observed that all 3.0 mm diameter implants failed the fatigue test, with better performed demonstrated by the implants of wider diameter [ 67 ]. Specifically in relation to the implant that showed the highest prevalence of fracture, the Z-Look3 of diameter 3.25 mm, a failure analysis study had already recommended that this implant should no longer be used clinically, and that modification of the implant geometry was needed [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive implant thread depth is not recommended, as surgical placement might generate high bending forces on the implant body when engaging the bony perimeter of the osteotomy, especially in patients with dense bone (Figure 1) [48]. Additionally, zirconia implants with a narrow diameter (<3.75 mm) have been reported to have a higher incidence of fracture compared to implants with a regular diameter [49][50][51]. The purpose of this mapping review is to present the breadth of evidence to answer the question, "What do studies reveal about the efficacy of zirconia implants?"…”
Section: Physical Properties Of Zirconiamentioning
confidence: 99%